2013
DOI: 10.1074/jbc.m112.444869
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Recruitment of Dynamin and BIN/Amphiphysin/Rvs (BAR) Domain-containing Proteins Leads to GTP-dependent Membrane Scission*

Abstract: Background: Dynamin and BAR domain proteins are major components of clathrin-mediated endocytosis and other membrane-trafficking events.Results: Dynamin is recruited to membranes by BAR domain proteins, which in turn rely on interaction with dynamin to bind membranes.Conclusion: Membrane binding by dynamin and BAR domain proteins is cooperative and stimulates dynamin and GTP-dependent membrane scission.Significance: Our results imply synergy of dynamin and BAR domain proteins to promote GTP-dependent vesicle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
147
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 48 publications
14
147
3
Order By: Relevance
“…3e). This observation suggests a positive feedback recruitment of the two proteins, a behaviour already reported for N-BAR proteins at high PtdIns(4,5)P 2 concentrations 15 .…”
Section: Bin1 Locally Recruits Pi-binding Motifs By Clustering Pismentioning
confidence: 49%
“…3e). This observation suggests a positive feedback recruitment of the two proteins, a behaviour already reported for N-BAR proteins at high PtdIns(4,5)P 2 concentrations 15 .…”
Section: Bin1 Locally Recruits Pi-binding Motifs By Clustering Pismentioning
confidence: 49%
“…Others have suggested that BAR domain-containing proteins are auto-inhibited due to intramolecular interactions (47)(48)(49)(50)(51)(52). Consequently, constructs lacking the SH3 domain could bind to and tubulate liposomes or generate membrane tubules more efficiently when overexpressed in cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, many questions remain concerning the mechanism of dynamin function and the roles of the numerous binding partners of dynamin including membrane curvature sensing/inducing BAR domain proteins such as amphiphysin and endophilin (Milosevic et al 2011;Meinecke et al 2013;Neumann and Schmid 2013) and proteins involved in actin polymerization/depolymerization (reviewed in Menon and Schafer 2013). Moreover, dynamin can also affect the earlier stages of CCP growth and invagination, although the precise mechanism by which it does so remains obscure (Loerke et al 2009;Mettlen et al 2009).…”
Section: Membrane Scissionmentioning
confidence: 99%